Species‐level image classification with convolutional neural network enables insect identification from habitus images. Issue 2 (24th December 2019) - Hansen, Oskar L. P.; Svenning, Jens‐Christian; Olsen, Kent; Dupont, Steen; Garner, Beulah H.; Iosifidis, Alexandros; Price, Benjamin W.; Høye, Toke T.
Abstract: Changes in insect biomass, abundance, and diversity are challenging to track at sufficient spatial, temporal, and taxonomic resolution. Camera traps can capture habitus images of ground‐dwelling insects. However, currently sampling involves manually detecting and identifying specimens. Here, we test whether a convolutional neural network (CNN) can classify habitus images of ground beetles to species level, and estimate how correct classification relates to body size, number of species inside genera, and species identity. We created an image database of 65, 841 museum specimens comprising 361 carabid beetle species from the British Isles and fine‐tuned the parameters of a pretrained CNN from a training dataset. By summing up class confidence values within genus, tribe, and subfamily and setting a confidence threshold, we trade‐off between classification accuracy, precision, and recall and taxonomic resolution. The CNN classified 51.9% of 19, 164 test images correctly to species level and 74.9% to genus level. Average classification recall on species level was 50.7%. Applying a threshold of 0.5 increased the average classification recall to 74.6% at the expense of taxonomic resolution. Higher top value from the output layer and larger sized species were more often classified correctly, as were images of species in genera with few species. Fine‐tuning enabled us to classify images with a high mean recall for the whole test dataset to species or higher taxonomic levels, however, with high variability. This indicates that some species are more difficult to identify because of properties such as their body size or the number of related species. Together, species‐level image classification of arthropods from museum collections and ecological monitoring can substantially increase the amount of occurrence data that can feasibly be collected. These tools thus provide new opportunities in understanding and predicting ecological responses to environmental change. Abstract : Species identity can be inferred from simple images of an extensive and highly accurate carabid beetle collection. Such image classification will be instrumental in efforts to increase the rate at which crucial occurrence data for insects are generated in the future.